2017
DOI: 10.1002/rmb2.12026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of various metformin treatments for women with polycystic ovary syndrome

Abstract: AimPolycystic ovary syndrome (PCOS) is an ovulatory disorder and insulin resistance and diabetes are involved in its pathophysiology. Metformin, an anti‐diabetic agent, has been reported to be useful to induce ovulation.MethodsMetformin treatment was classified into four types: (1) clomiphene–metformin combination treatment for clomiphene‐resistant patients; (2) clomiphene–metformin combination for clomiphene‐sensitive patients; (3) clomiphene–metformin combination for naïve patients; and (4) metformin monothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…One population of women in whom metformin use was studied prior to and throughout pregnancy are those diagnosed with polycystic ovarian syndrome (PCOS). Few adverse outcomes from metformin use in PCOS offspring were reported [39]. Yet one study found larger head circumference in metformin-exposed PCOS offspring correlated with maternal obesity [40].…”
Section: Discussionmentioning
confidence: 99%
“…One population of women in whom metformin use was studied prior to and throughout pregnancy are those diagnosed with polycystic ovarian syndrome (PCOS). Few adverse outcomes from metformin use in PCOS offspring were reported [39]. Yet one study found larger head circumference in metformin-exposed PCOS offspring correlated with maternal obesity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Follicular development and ovulation rate increased (33) Metformin and saxagliptin Improved insulin sensitivity, metformin and combine drugs showed a reduced in total cholesterol level, metformin shows decrease in the LDL-C and increase in HDL-C levels (34) Cinnamon, metformin and darchini…”
Section: Metformin and Clomiphenementioning
confidence: 99%